Dual Role of Dietary Curcumin Through Attenuating AFB1-Induced Oxidative Stress and Liver Injury via Modulating Liver Phase-I and Phase-II Enzymes Involved in AFB1 Bioactivation and Detoxification - Muhammad, Ishfaq; Wang, He; Sun, Xiaoqi; Wang, Xinghe; Han, Meiyu; Lu, Ziyin; Cheng, Ping; Hussain, Muhammad A.; Zhang, Xiuying (Frontiers in Pharmacology, 2018)
It is well understood that liver cytochrome p450 enzymes are responsible for AFB1 bioactivation, while phase-II enzymes regulated by the transcription factor nuclear factor-erythroid-2-related factor 2 (Nrf2) are involved in detoxification of AFB1. In this study, we explored the potential of curcumin to prevent AFB1-induced liver injury by modulating liver phase-I and phase-II enzymes along with Nrf2 involved in AFB1 bioactivation and detoxification. Arbor Acres broiler were divided into four groups including control group (G1; fed only basal feed), curcumin alone-treated group (G2; 450 mg/kg feed), AFB1-fed group (G3; 5 mg/kg feed), and curcumin plus AFB1 group (G4; 5 mg AFB1+450 mg curcumin/kg feed). After 28 days, liver and blood samples were collected for different analyses. Histological and phenotypic results revealed that AFB1-induced liver injury was partially ameliorated by curcumin supplementation. Compared to AFB1 alone-treated group, serum biochemical parameters and liver antioxidant status showed that curcumin supplementation significantly prevented AFB1-induced liver injury. RT-PCR and western blot results revealed that curcumin inhibited CYP enzymes-mediated bioactivation of AFB1 at mRNA and protein level. Transcription factor Nrf2, its downstream genes such as GSTA3, and GSTM2 mRNA, and protein expression level significantly upregulated via dietary curcumin. In addition, GSTs enzyme activity was enhanced with dietary curcumin which plays a crucial role in AFB1-detoxification. Conclusively, the study provided a scientific basis for the use of curcumin in broiler’s diet and contributed to explore the multi-target preventive actions of curcumin against AFB1-induced liver injury through the modulation of phase-I and phase-II enzymes, and its potent anti-oxidative effects.